Virtual Immortality — Paradise from the Machine (KULT_online, 2023)
In his book, Oliver Krüger engages with technical fantasies about overcoming death. More precisely, he observes the dynamics between religion, science fiction, and digitalization. He focuses on the currents of posthumanism and transhumanism and argues that virtuality becomes a fantastic space of possibility in which the spirit could exist permanently as an electrical entity (avatar).